PERAN GURU PAI DALAM PELAKSANAAN SHALAT DHUHA PADA PESERTA DIDIK DI SMA - Istiazah Ulima Hakim; Era Octafiona; Uswatun Hasanah; Zahra Rahmatika; Erni Yusnita (Qiro'ah : Jurnal Pendidikan Agama Islam, 2023)
An interesting phenomenon was discovered by researchers when conducting preresearch at SMA Negeri 1 Way Tenong, namely the Duha prayer by students in theschool prayer room even. though at that time the school was under renovation andlearning was divided into two sessions. They follow different extracurriculars. Inaddition, there is no school program that regulates the Duha prayer. As a school with ageneral education type, this phenomenon has attracted the attention of researchers. Thefacts on the ground strongly indicate that the PAI teacher is behind the scenes of theDhuha prayer of students. The type of research in this research is descriptive qualitativefield. This research uses a purposive sampling technique to determine informants. Datacollection techniques used are observation, interviews, and documentation. To test thevalidity of the data, researchers used source, technique, and time triangulation. Theresults showed that PAI teachers at SMA Negeri 1 Way Tenong played a role asorganizers, motivators, and facilitators in the implementation of Dhuha prayers for theirstudents.